Hubungan Kedisiplinan Pemakaian APD dan Pengetahuan K3 dengan Kejadian Kecelakaan Kerja pada Pekerja Bagian Pembahanan PT Prima Wana Kreasi Wood Industry - Fika Nurhasanah; Seviana Rinawati; Yulia Sari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
According to the data of Indonesian Employment Insurance Agency (BPJS) in 2020, the number of work accidents increased by 43.63%, 2019 as many as 114,235 cases increased to 177,161 cases in 2020. This studied aims to determine the relation of the discipline of PPE utilization and OSH knowledge with the incidence of work accidents by rectificating workers of PT Prima Wana Kreasi Wood Industry. This type of research was analytic observational with a cross sectional approach. Population in this study amounted to 62 people. The sampling technique used was total sampling. Data analysis in this studied used somers'd for bivariate analyzed and logistic regression test for multivariate analyzed. Bivariate test showed that there was a significant relationship between the discipline of PPE utilization and the incidence of work accidents (p = 0.000; r = -0.456). With the same test, there was a significant relationship between K3 knowledge and the incidence of work accidents (p = 0.000; r = -0.678). Multivariate test showed that the discipline of PPE utilization and OSH knowledge both had an effect on the incidence of work accidents, and it was known that OSH knowledge had a greater influence than years of service on the incidence of work accidents (p = 0.000 ; OR = 0.467; p = 0.000 ; OR = 0.048). Researchers suggest combining the variables that have been studied with uncontrollable confounding variables. Keywords: Discipline of PPE Utilization, OSH Knowledge, Incidence of Work Accidents